2(3) - 3 + 7 = 6 - 3 + 7 = 10
Answer:
>=
Step-by-step explanation:
since the shaded area is above the line y must be > or >= 1/4x-4, so the symbol must be > or >=. since the line isn't dashed, points on the line also fit the inequality meaning that the answer is >=
Answer:
12, 16, and 20
Step-by-step explanation:
These are the answers because:
1) Composite numbers mean numbers that are divisible by more than two numbers (1 and itself).
2) Multiples of 4 that are greater than 10 are: 12, 16, and 20 because they are all divisible by more than two numbers, they are greater than 10, and they are mutiples of 4. You can check if they are multiples of 4 by skip counting or multiplying: 4, 8, 12, 16, 20 or 4 x 1 = 4, 4 x 2 = 8, 4 x 3 = 12, 4 x 4 = 16, 4 x 5 = 20.
Therefore, the answers are: 12, 16, and 20
Hope this helps! :D
Answer:
the answee is 3
Step-by-step explanation:
Answer:
![y=\pm i \sqrt{7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20i%20%5Csqrt%7B7%7D)
Step-by-step explanation:
Given equation is ![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{3^2}{(y^2-16)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B3%5E2%7D%7B%28y%5E2-16%29%7D)
Factor denominators then solve by making denominators equal
![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{3^2}{(y^2-16)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B3%5E2%7D%7B%28y%5E2-16%29%7D)
![\frac{y}{\left(y-4\right)}-\frac{4}{\left(y+4\right)}=\frac{9}{(y+4)\left(y-4\right)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%5Cleft%28y-4%5Cright%29%7D-%5Cfrac%7B4%7D%7B%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B9%7D%7B%28y%2B4%29%5Cleft%28y-4%5Cright%29%7D)
![\frac{y\left(y+4\right)-4\left(y-4\right)}{\left(y-4\right)\left(y+4\right)}=\frac{9}{(y+4)\left(y-4\right)}](https://tex.z-dn.net/?f=%5Cfrac%7By%5Cleft%28y%2B4%5Cright%29-4%5Cleft%28y-4%5Cright%29%7D%7B%5Cleft%28y-4%5Cright%29%5Cleft%28y%2B4%5Cright%29%7D%3D%5Cfrac%7B9%7D%7B%28y%2B4%29%5Cleft%28y-4%5Cright%29%7D)
![y\left(y+4\right)-4\left(y-4\right)=9](https://tex.z-dn.net/?f=y%5Cleft%28y%2B4%5Cright%29-4%5Cleft%28y-4%5Cright%29%3D9)
![y^2+4y-4y+16=9](https://tex.z-dn.net/?f=y%5E2%2B4y-4y%2B16%3D9)
![y^2=9-16](https://tex.z-dn.net/?f=y%5E2%3D9-16)
![y^2=-7](https://tex.z-dn.net/?f=y%5E2%3D-7)
take squar root of both sides
![y=\pm \sqrt{-7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20%5Csqrt%7B-7%7D)
![y=\pm i \sqrt{7}](https://tex.z-dn.net/?f=y%3D%5Cpm%20i%20%5Csqrt%7B7%7D)
Hence final answer is
.